1985
DOI: 10.1007/bf03391910
|View full text |Cite
|
Sign up to set email alerts
|

A Behaviorist’s Response to the Report of the National Commission on Excellence in Education

Abstract: The National Commission on Excellence in Education was charged with the responsibility for examining the quality of education in America. Its report, "A Nation at Risk" (1983), contained a set of alarming facts about the status of American education. These were followed by a set of five major recommendations for improving the situation. They related to (1) content, (2) standards and expectations, (3) time, (4) teaching, and (5) leadership and support. The present paper examines each of the set of recommendatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1985
1985
1989
1989

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 24 publications
(20 reference statements)
0
3
0
Order By: Relevance
“…Finally, behavior analysts have attempted to extend their impact through strategies of developing large-scale interventions (e.g., Geller, Winett, & Everett, 1982) and disseminating their technologies to relevant audiences (e.g., Fawcett, Seekins, & Braukmann, 1981;Paine, Bellamy, & Wilcox, 1984;Seekins & Fawcett, 1984;Stolz, 1981). State laws and policies established by legislative bodies represent an important mechanism for amplifying the effects of behavior change efforts (see, for example, Carpenter, 1983;Greenberger, 1983;Maccoby, Kahn, & Everett, 1983;Seekins & Fawcett, 1986;Sulzer-Azaroff, 1985;Takanishi, DeLeon, & Pallack, 1983). As suggested by case studies and experimental research Jason & Rose, 1984) behavioral research data may even contribute to the enactment, implementation, and later revision of such laws.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, behavior analysts have attempted to extend their impact through strategies of developing large-scale interventions (e.g., Geller, Winett, & Everett, 1982) and disseminating their technologies to relevant audiences (e.g., Fawcett, Seekins, & Braukmann, 1981;Paine, Bellamy, & Wilcox, 1984;Seekins & Fawcett, 1984;Stolz, 1981). State laws and policies established by legislative bodies represent an important mechanism for amplifying the effects of behavior change efforts (see, for example, Carpenter, 1983;Greenberger, 1983;Maccoby, Kahn, & Everett, 1983;Seekins & Fawcett, 1986;Sulzer-Azaroff, 1985;Takanishi, DeLeon, & Pallack, 1983). As suggested by case studies and experimental research Jason & Rose, 1984) behavioral research data may even contribute to the enactment, implementation, and later revision of such laws.…”
Section: Resultsmentioning
confidence: 99%
“…The research on effective schools has not identified teacher or supervisor variables which are sufficient to produce the common characteristics of effective schools (Edmonds, 1979;Stallings, 1980). The literature in behavior analysis, however, has isolated functional pedagogical variables at the classroom level (SulzerAzaroff, 1985;Sulzer-Azaroff & Mayer, 1986). A few functional relationships between supervisor responses and client or student responses have been isolated in the behavior analysis literature also, but only in subunits of schools or human resource agencies (Greene, Willis, Levy, & Baily, 1976;Page, Iwata, & Reid 1982;Quillitch, 1975).…”
mentioning
confidence: 97%
“…A third strategy extends a suggestion made by Sulzer-Azaroff (1985). She notes that a diverse array of behavioral technologies exist for producing high levels of skilled academic performance, and that successes resulting from application of these methods "need to be communicated to educators, the public at large, and public policy makers" (Sulzer-Azaroff, 1985, p. 31).…”
Section: A Proactive Strategy: Advertising the Research Accelerationsmentioning
confidence: 92%